Enhancing attendance and student exam score based on mobile attendance application / Nurhafizah Ahmad ... [et al.] - Ahmad, Nurhafizah; Mohamed, Siti Asmah; Ul-Saufie, Ahmad Zia; Ahmat, Hasfazilah; Alias, Fadzilawani Astifar (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
In today’s digital era, it is possible to use the latest technology to improve student attendance and performance. The purpose of the present study is to determine the relationship between absenteeism and academic performance among Calculus students, as well as to measure the impact of class absence on the student’s final exam scores. Based on this, the use of appropriate strategy was employed, which is the mobile attendance application to reduce absenteeism among students in higher educational institution. The selection of sample was based on cluster sampling, involving the selection of 87 repeater students. The data collected were analyzed using quartile regression and independent sample t-test. The result of the findings revealed that the class absence has an impact on the student’s final exam scores. This is because, if the student was absences by 1 class, the final exam score is expected to decrease on average by 1.89%. Hence, findings show that the percentage of absences for the students with manual attendance was higher than the percentage of absences for the students with mobile attendance application. The application can help to reduce absenteeism by reminding students about recent attendance records.